1992
DOI: 10.1128/jb.174.3.921-929.1992
|View full text |Cite
|
Sign up to set email alerts
|

FIS-dependent trans activation of stable RNA operons of Escherichia coli under various growth conditions

Abstract: In Escherichia coli transcription of the tRNA operon thrU (tuJB) and the rRNA operon rrnB is trans-activated by the protein FIS. This protein, which stimulates the inversion of various viral DNA segments, binds specifically to a cis-acting sequence (designated UAS) upstream of the promoter of thrU (tuJB) and the P1 promoter of the rrnB operon. There are indications that this type of regulation is representative for the regulation of more stable RNA operons. In the present investigation we have studied UAS-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 30 publications
7
139
1
Order By: Relevance
“…Excision is inhibited by high concentrations of IHF [19,20]. Because the cellular levels of IHF and Fis proteins respond to growth conditions, these host-encoded factors have been proposed as the master signals for integration and excision [15,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Excision is inhibited by high concentrations of IHF [19,20]. Because the cellular levels of IHF and Fis proteins respond to growth conditions, these host-encoded factors have been proposed as the master signals for integration and excision [15,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mediating specialized site-specific DNA recombination events (1), this nucleoid-associated protein regulates transcription of ribosomal and tRNAs (2,3) and a growing number of structural genes (4 -16). Fis levels are transcriptionally regulated according to the nutritional conditions and the growth phase (17)(18)(19). A dramatic burst in fis mRNA levels is observed when stationary phase cells are outgrown in rich medium, which reach a peak during early logarithmic growth phase, decrease to much lower levels during late logarithmic growth phase, and become undetectable during stationary phase (17,18), an expression pattern that is closely followed at the protein level (17,19).…”
mentioning
confidence: 99%
“…Fis levels are transcriptionally regulated according to the nutritional conditions and the growth phase (17)(18)(19). A dramatic burst in fis mRNA levels is observed when stationary phase cells are outgrown in rich medium, which reach a peak during early logarithmic growth phase, decrease to much lower levels during late logarithmic growth phase, and become undetectable during stationary phase (17,18), an expression pattern that is closely followed at the protein level (17,19). The fis mRNA half-life is short (about 2 min) and does not vary appreciably throughout the period of growth phase-dependent expression, indicating that the fis mRNA expression pattern is not attributed to changes in mRNA turnover rates but is primarily attributed to transcriptional control (20).…”
mentioning
confidence: 99%
“…Global transcriptional factors can also be an important link between the environment and the physiological state of bacteria (MartĂ­nez-Antonio & Collado-Vides, 2003). For example, Fis (factor for inversion stimulation) triggers the fast growth of Escherichia coli in the presence of a sudden abundance of nutrients in the environment (Ball et al, 1992;Mallik et al, 2004;Nilsson et al, 1992). Bradley et al (2007) found that apart from the 231 genes that Fis regulates in E. coli, it activates the expression of a further 38 flagellar and motility genes as well.…”
Section: Introductionmentioning
confidence: 99%